GANTI KERUGIAN IMMATERIIL TERHADAP PERBUATAN MELAWAN HUKUM DALAM PRAKTIK: PERBANDINGAN INDONESIA DAN BELANDA - Rai Mantili (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2019)
Article 1365 of the Civil Code states that an unlawful act that carries a loss to another person obliges the person who because of his mistake to issue the loss, compensates for the loss. The formulation regarding unlawful acts is not explained and only provides a basis for submitting compensation based on unlawful acts. The forms of loss in cases of acts against the law usually consist of two forms, namely material losses and immaterial losses. The research method in this research is normative juridical. Through the research outlined in the form of this article, it is hoped that the concept of immaterial compensation in Indonesia can be formed in order to create legal certainty in a court decision. The results of the study confirm that the absence of regulation regarding compensation for immaterial losses against the law causes different interpretations in the judge's decision. What will be explained in this article is about the regulation of immunity compensation in cases of illegal acts in practice in Indonesia and regarding the regulation of immunity compensation in acts against the law in the Netherlands.